Concomitant occurrence of neurofibromatosis type I and lobular capillary hemangioma in the oral cavity: a case report - Rakhi ISSRANI (International Arab Journal of Dentistry (IAJD), 2013)
Neurofibromatosis type I is one of the most common autosomal dominant inherited disorders associated with deletion, insertion, or mutation in the NF-1 gene. Neurofibromas are the hallmark of the neurofibromatosis type I and usually appear during childhood or adolescence after the emergence of “café au lait” spots. Despite their occurrence in the head and neck region, neural sheath tumors are rarely seen in the oral cavity. Lobular capillary hemangioma is a histologic variant of pyogenic granuloma which is a common benign vascular lesion of the skin and mucosa. It is neither infective / purulent nor granulomatous as the name might suggest - rather a reactive enlargement that is an inflammatory response to local irritation.In the present study, we report a rare case of concomitant occurrence of neurofibromatosis type I and lobular capillary hemangioma in a fifteen-year-old Indian female who presented with a gingival overgrowth in her maxillary anterior region. The lesion was excised and histopathological report confirmed the diagnosis. To the best of our knowledge this is the first case in english literature where there was a parallel occurrence of neurofibromatosis type I and lobular capillary hemangioma in the oral cavity.